FINANCIAL SANCTIONS IN THE CONTEXT OF FORMING A SECURE SPACE: THEORETICAL FOUNDATIONS - HNATKIVSKYI, Bohdan (Scientific journal «World of Finance», 2024)
Introduction. Democratic countries apply unprecedented pressure with financial sanctions to maintain international order if a country systematically violates international norms and established rules. Countries impose financial sanctions to protect their own interests, such as national security, economic security, or defense against external threats. The impact of financial sanctions can have a synergistic effect and depends on the geopolitical context, the effectiveness of the sanctions policy, and the countries' response to the sanctions. The effectiveness of financial sanctions depends on the political context of application and the chosen strategy of international pressure on the target country.The purpose of the article is to deepen the theoretical and applied principles of applying financial sanctions to regulate and scale financial motivation to de-escalate military conflicts, taking into account the coordinated actions of democratic countries to create a safe space.Results. The necessity of applying financial sanctions with a focus on the political will and diplomatic pressure of democratic countries and the motivation of the aggressor country is substantiated. The classification of financial, tangible and intangible assets that are subject to sanctions is considered. For the adequate compliance of financial sanctions, the assessment of their effectiveness in specific situations of escalation of military conflict or growing threat to national sovereignty has been studied. Systematized sanctions against economic agents, in particular with a corporate ownership structure to track the placement of securities and changes in corporate behavior. The expediency of identifying methods, forms and tools of financial sanctions for monitoring by regulators has been determined.Prospects. The effectiveness of preventive measures to increase remedial pressure requires the systematic application of financial, procedural and procedural sanctions. The essential advantages of financial sanctions are the speed of implementation, regulation and monitoring. It is important to distinguish financial sanctions from other related concepts (procedures), which in their essence are not sanctions and weaken the economic and political restrictions of aggressive and repressive regimes.